Investigation of the effects of immersion period of simulated body fluid on the morphology and structural properties of Fe/Ni co-doped chlorapatites - Keser, Serhat; Ateş, Tankut; Bulut, Niyazi; Kaygılı, Omer (Niyazi BULUT, 2023)
In this study, chlorapatite (ClAp) samples co-doped with Fe and Ni at different amounts were synthesized using a wet chemical method. The as-produced samples were immersed in simulated body fluid (SBF) for 14 and 28 days. The samples were characterized before and after soaking in SBF, and their morphologies and structural properties were compared to each other. It was observed that the immersion period in SBF and the amount of Fe and Ni affected the morphology and structural properties of the ClAp samples.
Keywords: Material Production Technologies; Malzeme Üretim Teknolojileri